2013
DOI: 10.1242/bio.20133772
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of lung development in the amphibian, Xenopus laevis

Abstract: SummaryContrary to previous studies, we found that Xenopus laevis tadpoles raised in normoxic water without access to air can routinely complete metamorphosis with lungs that are either severely stunted and uninflated or absent altogether. This is the first demonstration that lung development in a tetrapod can be inhibited by environmental factors and that a tetrapod that relies significantly on lung respiration under unstressed conditions can be raised to forego this function without adverse effects. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…The early lung use is important in determining the probability of a successful metamorphosis. 66,67 Before metamorphosis, Xenopus lung development at the cellular and molecular levels is comparable to embryonic stages of mouse respiratory system development between embryonic days 8.5 and 10.5. Therefore, it could be considered as a model to define the programs controlling early respiratory system development.…”
Section: Discussionmentioning
confidence: 99%
“…The early lung use is important in determining the probability of a successful metamorphosis. 66,67 Before metamorphosis, Xenopus lung development at the cellular and molecular levels is comparable to embryonic stages of mouse respiratory system development between embryonic days 8.5 and 10.5. Therefore, it could be considered as a model to define the programs controlling early respiratory system development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well known role as a model for early patterning events and posterior foregut development, Xenopus has emerged as a good model system for studying development of the respiratory system [59, 60]. Unique among aquatic model systems, Xenopus embryos rapidly develop lungs in the first few days of embryogenesis, which at the molecular and histological level are similar to early mouse lungs [60••].…”
Section: Lung and Thyroid Developmentmentioning
confidence: 99%
“…Though the pathways by which most factors exert their influence remain unstudied, some appear to act through chemical cues and visual and tactile stimuli (Griffiths et al, ; Rot‐Nikcevic et al, ; Gouchie et al, ; Schoeppner and Relyea, ) and many act through complex networks of interactions (Relyea, ; Indermaur et al, ; Brown et al, ; Searle et al, ). Adding to the list, Rose and James () found that raising Xenopus tadpoles in cages that prevent them from breathing air delays the completion of metamorphosis.…”
mentioning
confidence: 99%
“…Nonetheless, there are at least two justifications for understanding how the elimination of air breathing might affect tadpole growth and developmental rates. First, air‐deprived (AD) Xenopus tadpoles have been proposed as an experimental model for investigating the changes in gene expression, cell differentiation, and lung morphogenesis that are triggered by the initial entry of air into the lung (Rose and James, ). This event, which shall be referred to here as lung inflation, is inherently difficult to study because it coincides with hatching or birth in amniotes and occurs at variably timed larval stages in amphibians (Wassersug and Seibert, ; Burggren and Just, ; Ultsch et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation